A review of the utility of tacrolimus in the management of adults with autoimmune hepatitis. (2nd January 2019) - Hanouneh, Mohamad; Ritchie, Michael M.; Ascha, Mona; Ascha, Mustafa S.; Chedid, Alice; Sanguankeo, Anawin; Zein, Nizar N.; Hanouneh, Ibrahim A.
Abstract: Background: There is paucity of data on alternative drug therapies for patients with autoimmune hepatitis (AIH). Tacrolimus (TAC) is a promising salvage agent. We present a review of TAC therapy in AIH patients. Methods: A search for studies with keywords 'autoimmune hepatitis' and 'tacrolimus' was performed. Reviews, studies of AIH post-transplant and AIH in children were excluded. Diagnosis of AIH was based on criteria established by the International Autoimmune Hepatitis Group. Complete biochemical response was defined as normalisation of aspartate aminotransferase (AST <45) and alanine aminotransferase (ALT <50). No biochemical response was defined as failure to return to normalisation at the end of follow-up. Demographic information and details of pre- and post-treatment liver biopsy were collected. Results: Seven articles achieved the inclusion criteria and reported data for a total of 162 adult patients. The majority of studies reported average ages approximately 35 years old. Treatment duration ranged from 1 to 136 months. Indications for therapy were mostly AIH refractory to steroid treatment or inability to tolerate standard steroid treatment. Eighty-three patients (51.2%) were reported to have pre-therapy liver biopsy. Of 49 patients for whom stage was reported, 6 patients were stage 1, 16 were stage 2, 14 were stage 3 and 13 were stage 4. Of 40 patients for whom grade was reported, 1 patient was grade 0, 3 were grade 1, 9 were grade 2, 14 were grade 3 and 13 were grade 4. Dosing regimens were between 1 and 8 mg/day. Target trough TAC serum concentrations ranged from 0.5 to 10.7 ng/mL TAC was discontinued in 28 (17.3%) patients for various reasons. Renal function remained stable in most patients. One hundred and twenty-one patients (74.7%) demonstrated complete biochemical response to treatment. Post-therapy liver biopsy was obtained for 30 (18.5%) patients, and 25 (15.4%) of these patients were noted to have histological remission according to the grade of inflammation or stage of fibrosis. Conclusion: TAC is relatively effective in the treatment of AIH refractory to traditional therapy. It appears that liver function can be enhanced at a minimal cost to renal function. Key Points There is a cohort of patients with autoimmune hepatitis (AIH) who do not respond to standard therapy. Alternative treatment options for these patients have been explored, but outcomes have not been comprehensively examined. We report the use and efficacy of tacrolimus (TAC) in patients with AIH. We found that TAC can be safely and effectively used in patients with AIH with minimal side effects. TAC can be a potential treatment option for patients with AIH refractory to standard therapy.